2007
DOI: 10.1126/science.1136020
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Energy Scales at a Quantum Critical Point

Abstract: We report thermodynamic measurements in a magnetic-field-driven quantum critical point of a heavy fermion metal, YbRh2Si2. The data provide evidence for an energy scale in the equilibrium excitation spectrum that is in addition to the one expected from the slow fluctuations of the order parameter. Both energy scales approach zero as the quantum critical point is reached, thereby providing evidence for a new class of quantum criticality.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

56
331
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 235 publications
(391 citation statements)
references
References 31 publications
56
331
0
1
Order By: Relevance
“…1 which is adapted from Refs. [13,14]. The small ordering temperature in zero magnetic field already demonstrates that the RKKY interaction is only slightly ahead in the competition of the energy scales.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…1 which is adapted from Refs. [13,14]. The small ordering temperature in zero magnetic field already demonstrates that the RKKY interaction is only slightly ahead in the competition of the energy scales.…”
Section: Introductionmentioning
confidence: 94%
“…In the unconventional Kondo-breakdown scenario, by contrast, the quasiparticles disintegrate and, consequently, the Fermi-surface volume is expected to undergo a discontinuous change at the QCP. Based on this, measurements which probe the [13,14]. Both, the Néel temperature T N and the Landau-Fermi-liquid temperature T LFL were obtained from resistivity measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the Fermi surface volume abruptly changes at the QCP. This crossover was followed up to 500 mK introducing a new energy scale which is confirmed by other transport properties as well as thermodynamic quantities [5]. In order to understand differences found in R H ðTÞ of newer samples we extended the measurements to samples of varying quality including the sample used in Ref.…”
mentioning
confidence: 93%
“…The anticipated behavior of the spin relaxation rate Γ Q at the ordering wave vector is (for d = 3) Γ Q ∼ T 3/2 , which has indeed been observed in one heavy fermion system [6]. There are however a number of observations that cannot be explained within the SDW approach [7,8,9,10]. In CeCu 6−x Au x , at its critical concentration x c ≈ 0.1, the spin relaxation rate is linear in temperature, and the order-parameter susceptibility singularly depends on temperature and frequency with a fractional exponent [7].…”
Section: Introductionmentioning
confidence: 88%